1997
DOI: 10.1002/(sici)1098-2264(199705)19:1<29::aid-gcc5>3.3.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Significance of chromosome arm 14q loss in nonpapillary renal cell carcinomas

Abstract: We examined 88 nonpapillary renal cell carcinomas for allelic loss at chromosome arm 14q and correlated the results to size, grade, and stage of these tumors. Fourteen highly polymorphic microsatellite markers on the long arm of chromosome 14 were used for deletion mapping. Loss of heterozygosity (LOH) at the smallest overlapping segment of 14q24.2-qter was seen in 42 of 88 tumors. There was no significant correlation between frequency of 14q LOH and size of tumors (P = 0.11). LOH was frequently seen in grade … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…In renal cell carcinomas, LOH of 14q is often combined with a higher nuclear grading and staging. 48 In summary, we could demonstrate significant qualitative and quantitative genetic changes associated with clinical stage and morphological phenotype. The broad spectrum of phenotypically heterogeneous DCIS with significantly different aberrations raises the question of multiple pathways for invasive breast cancer with DCIS as a precursor lesion.…”
Section: Discussionmentioning
confidence: 75%
“…In renal cell carcinomas, LOH of 14q is often combined with a higher nuclear grading and staging. 48 In summary, we could demonstrate significant qualitative and quantitative genetic changes associated with clinical stage and morphological phenotype. The broad spectrum of phenotypically heterogeneous DCIS with significantly different aberrations raises the question of multiple pathways for invasive breast cancer with DCIS as a precursor lesion.…”
Section: Discussionmentioning
confidence: 75%
“…(18) Corresponding to this, the frequent occurrence of loss of heterozygosity (LOH) on the long arm of chromosome 14, where Dicer resides, has been reported in lung cancers, (19,20) while a number of studies have also indicated that this chromosomal region is often affected in various other human cancers. (21)(22)(23)(24)(25)(26) It is interesting that LOH on 14q appears to be related to tumor progression of colon cancer, with a higher incidence of this anomaly in metastatic sites than in primary tumors. (27) Accumulating evidence supports the notion that the prognostic impact of reduced Dicer expression observed in our study might have a functional role in the development of lung cancers rather than being a mere surrogate marker.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Schwerdtle et al have found that marker D14S258 also exhibits frequent allelic loss in renal oncocytomas, implicating a locus for a tumour suppressor gene possibly involved in different tumours (Schwerdtle et al, 1997). Furthermore, 14q24-q32 has been found to be the smallest overlapping segment of deletions in both nonpapillary renal cell carcinoma and meningiomas (Simon et al, 1995;Herbers et al, 1997).…”
Section: Discussionmentioning
confidence: 99%